ANALISIS PENGARUH CURRENT RATIO, FIRM SIZE, DEBT TO ASSET, DAN DEBT TO EQUITY TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN FIRM AGE SEBAGAI VARIABEL KONTROL (Studi Pada Perusahaan Sub Sektor Property dan Real Estate Terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Kartika Azzahra; Raden Djoko Sampurno (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze the effect Current Ratio, Firm Size, Debt to Asset Ratio, and Debt to Equity Ratio on the company's financial performance as measured by Return on Assets with Firm Age as a control variable in the 2017-2021 period. This study was conducted using multiple linear regression analysis method with data processing software used is IBM SPSS 25 to analyze the effect Current Ratio, Firm Size, Debt to Asset Ratio, and Debt to Equity Ratio to Return on Assets with Firm Age as control variable. This study uses secondary data sourced from the publication of quarterly and annual financial reports of sub-sector companies property and real estate listed on the Indonesia Stock Exchange in the 2017-2021 period. The sample used in this study was taken by purposive sampling method with a total sample of 50 companies with 250 observations. The results of this study indicate that Current Ratio (CR) and Debt to Asset Ratio (DAR) with the influence of Firm Age as the control variable has a significant negative effect on Return on Assets (ROA). Firm Size (SIZE) with the influence of Firm Age as the control variable has a significant positive effect on Return on Assets (ROA), meanwhile Debt to Equity Ratio has a negative but not significant effect on Return on Assets (ROA)